Multiple but asymmetric bank financing : the case of relationship lending - Ralf Elsas; Frank Heinemann; Marcel Tyrell (Center for Economic Studies and ifo Institute (CESifo), 2004)
Empirical evidence suggests that even those firms presumably most in need of monitoringintensive financing (young, small, and innovative firms) have a multitude of bank lenders, where one may be special in the sense of relationship lending. However, theory does not tell us a lot about the economic rationale for relationship lending in the context of multiple bank financing. To fill this gap, we analyze the optimal debt structure in a model that allows for multiple but asymmetric bank financing. The optimal debt structure balances the risk of lender coordination failure from multiple lending and the bargaining power of a pivotal relationship bank. We show that firms with low expected cash-flows or low interim liquidation values of assets prefer asymmetric financing, while firms with high expected cash-flow or high interim liquidation values of assets tend to finance without a relationship bank.
Keywords: G21; G78; G33; 330; relationship lending; multiple bank financing; lender coordination; Fremdkapital; Kredit; Bank; Finanzierung; Lieferanten-Kunden-Beziehung; Theorie